Pengaruh Ekstrakurikuler Drumband terhadap Disiplin Bermusik Anak - Lirana Suryaning Harlambang, Ayu; Fitriyono, Angga; Yuandana, Tarich (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
The objective of this study is to examine the impact of extracurricular drumband activities on children's musical discipline. The research employs a quantitative approach utilizing a one-group pretest-posttest experimental design. Data were collected through pre-research interviews, documentation, and validated observations. The sample was drawn using a saturated sampling technique, encompassing the entire population, resulting in 31 respondents from TK Anna Husada Bangkalan. The findings indicate that the observation sheet's validity, comprising 8 items, reached a value of 87.5%, categorizing it as highly valid. Data analysis included normality tests and hypothesis testing using t-tests. The normality test results revealed that the pre-test value was 0.098 > 0.05 and the post-test value was 0.078 > 0.05, indicating a normal data distribution. The hypothesis test showed that the calculated t-value (t-count) was 41.375, exceeding the critical t-value (t-table) of 2.04227, leading to the acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (H0). Consequently, it can be concluded that extracurricular drumband activities positively influence children's musical discipline. This research suggests that incorporating drumband activities in early childhood education can significantly enhance children's musical discipline. Schools and educators might consider integrating such extracurricular activities into their curriculum to foster better discipline and potentially improve overall academic and personal development outcomes for children. Future research could explore long-term effects and the impact of similar activities on other areas of children's growth.